Cell-Type Specific Deletion of CB2 Cannabinoid Receptors in Dopamine Neurons Induced Hyperactivity Phenotype: Possible Relevance to Attention-Deficit Hyperactivity Disorder - Canseco-Alba, Ana; Sanabria, Branden; Hammouda, Mariam; Bernadin, Rollanda; Mina, Marizel; Liu, Qing-Rong; Onaivi, Emmanuel S. (Frontiers in Psychiatry, 2022)
DAT-Cnr2 mice are conditional knockout (cKO) animals that do not express cannabinoid CB2 receptors (CB2R), in midbrain dopamine transporter (DAT) expressing neurons. The hyperactive phenotype of DAT-Cnr2 cKO mice were paradoxically reduced by low dose of amphetamine. Here, we report on the locomotor activity analysis in male and female adolescent (PND 30±2) mice in basal conditions and in response to different doses of amphetamine, using the Open Field (OF) and Elevated Plus-Maze (EPM) tests and the Novel Object Recognition (NOR) task. Results showed that both male and female adolescent DAT-Cnr2 mice displayed significant increases in distance traveled in the OF test compared with WT mice. However, 2 mg/kg dose of amphetamine reduced the distance traveled by the DAT-Cnr2 but was increased in the WT mice. In the EPM test of anxiety-like behavioral responses, DAT-Cnr2 spent more time in the open arms of the maze than the WT mice, suggesting a reduction in anxiety-like response. DAT-Cnr2 mice also showed significant increases in the number of unprotected head dips in the maze test. This hyperactivity and risky behavior could be interpreted as impulsivity characteristically comorbid with addiction. Both DAT-Cnr2 and WT were able to recognize the new object in the NOR task, but the exploration of the DAT-Cnr2 was less than that of the WT mice. Following the administration of 2 mg/kg of amphetamine, the similarities and differential performances of the DAT-Cnr2 and WT mice in the EPM test and NOR task was possibly due to increase in attention, and a reduction in the unprotected head dips. In both tests, amphetamine reduced the number of overall entries with a slight increase in the activity of the WT mice. Microglia activation detected by Cd11b immunolabelling was enhanced in the dentate gyrus and Cornu Ammonis (CA) in DAT-Cnr2 than in WT mice, implicating neuro-immune modulatory effects of CB2R. The results of these follow up studies on DAT-Cnr2 cKO mice that display continuous hyperactive phenotype allows us to conclude that the cell-type specific deletion of CB2R in midbrain dopaminergic neurons can be proposed as a possible model of ADHD and addiction.